Development of a CO2e quantification method and of solutions for reducing the greenhouse gas emissions of construction machines - Ays, Isabelle Charlotte (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2022)
This work focuses on the development of a quantification method for GHG (CO2e) emissions from construction machines. The method considers CO2e reduction potentials in the time past-present-future, through influencing factors from six pillars: Machine efficiency, process efficiency, energy source, operating efficiency, material efficiency and CCS. In addition, transformation solutions are proposed to reduce GHG emissions from construction machines like liquid methane, fuel cell drive or CCS.